2020
DOI: 10.1111/bjep.12394
|View full text |Cite
|
Sign up to set email alerts
|

To what extent does punishment insensitivity explain the relationship between callous‐unemotional traits and academic performance in secondary school students?

Abstract: Background. Callous-unemotional (CU) traits are related to low achievement but not to deficits in verbal ability, commonly regarded as a major risk factor for poor academic outcomes in antisocial youth. This suggests that CU traits may have utility in explaining heterogeneous risk pathways for poor school performance in antisocial children. Reduced sensitivity to teacher discipline has been suggested as a potential explanation for the association between CU traits and low achievement, given its importance in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 59 publications
1
0
0
Order By: Relevance
“…Similar to past research highlighting the role of punishment insensitivity in explaining the link between CU traits and low academic achievement (Hwang et al, 2021 ), our results showed that poorer academic engagement was related to higher CU traits and children’s negative responses to discipline. However, the significance of CU traits as a predictor disappeared after controlling for disruptive behavior, instructional methods, and other demographic variables.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to past research highlighting the role of punishment insensitivity in explaining the link between CU traits and low academic achievement (Hwang et al, 2021 ), our results showed that poorer academic engagement was related to higher CU traits and children’s negative responses to discipline. However, the significance of CU traits as a predictor disappeared after controlling for disruptive behavior, instructional methods, and other demographic variables.…”
Section: Discussionsupporting
confidence: 91%